STYLES OF SEDIMENTATION BENEATH SVALBARD VALLEY GLACIERS UNDER CHANGING DYNAMIC AND THERMAL REGIMES - Glasser N.F.; Hambrey M.J. (My University, 2001)
Glacier beds provide crucial information concerning past and present ice dynamics and thermal regime. In this paper we present structural and sedimentological data from four valley glaciers (Austre Lovénbreen, Midtre Lovénbreen, Vestre Lovénbreen and Austre Brøggerbreen) on Brøggerhalvøya, NW Spitsbergen. The main focus of this paper is Midtre and Austre Lovénbreen, two typical High-Arctic land-based polythermal valley glaciers; the former has a long record of documentation regarding its response to twentieth century climatic warming. Structural mapping on the glacier surface and analysis of sediments in the proglacial area of Midtre Lovénbreen indicate that the dynamic regime and thermal structure of the glacier have changed through time. Dynamically, Midtre Lovénbreen was once heavily crevassed and relatively fast moving, but now is virtually crevasse-free and slow moving. The sedimentary record indicates that extensive areas of this glacier were wet-based when it was in a more advanced state, probably at its Neoglacial maximum (late nineteenth/early twentieth centuries). During this advance, a thin deforming layer of diamicton, commonly fluted, was draped over the existing morphology in the presently exposed proglacial area. This morphology consisted of large streamlined ridges aligned parallel to ice flow. Erosion of the underlying bedrock appears to have been limited. Radio-echo soundings of the glacier show that, at present, it is characterized by a polythermal basal thermal regime, with wet-based subglacial conditions only beneath its thicker parts. Modification of the bed is limited under this thermal regime and, as a result, the supraglacial environment dominates modern sedimentation. Comparative studies on Austre Lovénbreen, which also is probably polythermal, indicate similar sedimentary characteristics and facies associations, although here there are much more extensive areas of striated bedrock indicative of former basal sliding. In contrast both Austre Brøggerbreen and, by analogy, Vestre Lovénbreen are known to be predominantly cold-based. Collectively, these four glaciers suggest a trend of glacier recession and thinning accompanied by a change in thermal regime from predominantly wet-based, through partly frozen, to completely frozen. This study suggests that Svalbard valley glaciers have several dynamic modes and that glaciers switch between these modes largely as a reaction to changes in mass balance.
Keywords: Svalbard; glacial sedimentation; dynamics; thermal regime; mass balance